Noticing and Noting: Teaching Students With EBD to Effectively Self-Monitor. (August 2019) - Lastrapes, Renée E.; Mooney, Paul
Self-monitoring interventions can be effective components in the specially designed instruction programs of students with emotional and behavioral disorders. This article provides a self-monitoring definition, rationale for use, and summary of research supporting use of the empirically supported intervention. It also includes a description of how to plan, implement, and evaluate implementation of a self-monitoring procedure and performance tips for professionals.